Assessment of Side Effects of COVID-19 Vaccine Among General Population attending Kalar COVID-19 Vaccine Centers, Sulaimaniyah, Iraq - Amin, Baxan Farman Hama; Muhammed, Omed Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: The SARS-CoV-2 virus is an extraordinary virus that has become a severe public health problem; the symptoms that usually end in mortality include fever, dry cough, tiredness, shortness of breath, chills and etc. Objectives: This study examines the potential relationship between sociodemographic factors and the side effects of COVID19 vaccination. Patients and methods: A total of 511 participants were included in this study and were distributed according to their sociodemographic characteristics, including gender, age, marital status, education level, and occupation. Data on vaccination side effects were collected at 24 hours, 72 hours, and one week after vaccination. Statistical analysis was performed to identify significant associations between sociodemographic factors and vaccination side effects. Results: most patients were aged between (40-65 years), females, married, housewives, illiterate, and lived in an urban area. The study's findings revealed insufficient awareness in >50% of patients. A highly significant correlation between awareness and the level of education has been founded and also a significant association with age, gender, and profession was found. At the same time, marital status and residency didn't affect the awareness. Conclusions: This study highlights the importance of considering sociodemographic factors in assessing COVID19 vaccine side effects. The findings show that occupation and gender may significantly predict vaccine side effects and should be considered when evaluating vaccine safety and efficacy
Keywords: COVID19; vaccination; side effects; sociodemographic factors; occupation; gender